Sclerostin and OPG/RANK-L system take part in bone remodeling in patients with acromegaly - Halupczok-Żyła, Jowita; Jawiarczyk-Przybyłowska, Aleksandra; Bolanowski, Marek (Frontiers in Endocrinology, 2024)
IntroductionAcromegaly is a disease characterized by enhanced bone turnover with persistently high vertebral fracture risk. Sclerostin is a glycoprotein, which acts as an inhibitor of bone formation and activates osteoclast-mediated bone resorption. The osteoprotegerin (OPG)/receptor activator for the nuclear factor κ B ligand (RANK-L) system is crucial for controlling bone metabolism.ObjectiveThe study aimed primarily at evaluating sclerostin, OPG, and RANK-L concentrations in patients at different stages of acromegaly activity. The secondary aim was to identify an association of sclerostin with the OPG/RANK-L system and bone mineral density (BMD).Materials and methodsThe study enrolled 126 patients aged 40 to 80 years, including 72 patients with acromegaly and 54 controls (CG). The acromegaly patients were further classified into the following subgroups: active acromegaly (AA), controlled acromegaly (CTA), and cured acromegaly (CA). Blood samples were taken from the participants to measure sclerostin, OPG, RANK-L, growth hormone (GH), and insulin-like growth factor-1 (IGF-1). Dual-energy X-ray absorptiometry was performed at the lumbar spine and hip.ResultsSignificantly lower sclerostin concentrations were observed in acromegaly patients compared with CG (AA, CTA, CA, CTA+CA, AA+CTA+CA vs CG; p < 0.001). Significant differences in OPG concentrations were revealed between the following groups: CTA vs CA (p=0.002), CTA vs CG (p<0.001), CTA+CA vs. CG (p<0.001), and AA+CTA+CA vs. CG (p<0.001). There were no significant differences in RANK-L concentrations between studied groups, regardless of the adopted classification (p>0.05). There were no statistically significant correlations between sclerostin and GH/IGF-1 or BMD. In the AA+CTA+CA group, there was a statistically significant positive correlation between SCL and OPG concentrations (r=0.271; p=0.022). A significant negative correlation between SCL and RANK-L was found in the AA group (r=-0.738; p=0.046).ConclusionsPatients with acromegaly have lower sclerostin concentrations than healthy controls, which may be a result of a compensatory mechanism to increased bone loss. The influence of the GH/IGF-I axis on bone remodeling may be mediated in part by the OPG/RANK-L system. The interaction between SCL and OPG/RANK-L system in acromegaly should be further elucidated.